jangibaev.n@mail.ru EFFECTIVE GAME TECHNOLOGIES FOR PRESCHOOLERS’ SPEECH: EFFECTIVE GAME TECHNOLOGIES FOR PRESCHOOLERS’ SPEECH - Jangibaev, Nursulton (Журнал иностранных языков и лингвистики, 2022)
The article indicates the need for a correct approach to the development of speech of preschoolers using modern gaming technologies. There are different types of didactic games: games with objects (toys); board-printed games; word games, and in practice, all the tasks of the speech development of preschool children can be realized on the basis of a theatrical game. The author of the article strongly emphasizes that the formation of grammatically correct, lexically rich and phonetically pure speech in children is one of the most important tasks in the general system of education and training of a child.